Positive Solutions for Fourth-Order Nonlinear Differential Equation with Integral Boundary Conditions - Qi Wang; Yanping Guo; Yude Ji (Discrete Dynamics in Nature and Society)
This paper investigates the existence and nonexistence of positive solutions for a class of fourth-order nonlinear differential equation with integral boundary conditions. The associated Green's function for the fourth-order boundary value problems is first given, and the arguments are based on Krasnoselskii's fixed point theorem for operators on a cone.